Ocurrencia eStacional de Coccidophilus citricola y de sus principales presas en una plantacion de naranjos - Guerreiro, J.C.=700 1 Filho, E.V.; Busoli, A.C.; Ruiz, M.G.
(Es, En)
Ilus., 26 ref.
Keywords: FRUTAS CITRICAS; INSECTA; COCCOIDEA; DEPREDADORES; ENEMIGOS NATURALES; COSTA RICA; COCCIDOPHILUS CITRICOLA; ESCAMAS